Teachers' Imperative Speech Acts in the Teaching and Learning Process at SMP - Rahmadani A. Dai; Yunidar Yunidar; Julia Marfuah; Syamsuddin Syamsuddin; Arum Pujining Tyas (Global Education Journal, 2026)
Language is a tool of social interaction or a tool of communication between fellow humans. This research aims to discuss how the form, function, and form of teacher imperative speech actions in the teaching and learning process at SMP Negeri 2 Parigi. The method carried out in this study is qualitative research. The data collection carried out was by one observation, two records, three views and notes. The subject of this research is the teacher's speech in the teaching and learning process at SMP Negeri 2 Parigi. The data analysis technique carried out in this study includes three stages, namely, one data reduction, two data presentation, and three conclusions. The results of the study showed that the form of mandatory teacher speech in the teaching and learning process at SMP Negeri 2 Parigi consisted of one request speech consisting of three data, two permission speeches consisting of three data, three invitation speeches consisting of two data, four command speeches consisting of six data, and five prohibition speeches consisting of four data. The functions contained in this study follow from the form of imperative speech and strategies contained in this study, namely one direct strategy and an indirect strategy. Based on these findings, it can be concluded that teachers' imperative speech actions have an important role in supporting the success of the teaching and learning process, both as a communication tool and as an effective interaction between teachers and students.